2019
DOI: 10.1016/j.atmosenv.2019.116988
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of wintertime O3 and NOx formation using vector autoregressions

Abstract: Concentrations of 11 species are reported from continuous measurements taken during a wintertime field study in Utah. Time series data for measured species generally displayed strong diurnal patterns. Six species show a diurnal pattern of daytime maximums (NO, NO y , O 3 , H 2 O 2 , CH 2 O 2 , and Cl 2), while five species show a diurnal pattern of night time maximums (NO 2 , HONO, ClNO 2 , HNO 3 , and N 2 O 5). Vector autoregression analyses were completed to better understand important species influencing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In this case, the enriched NO 2 atmosphere and dark environment were responsible for generating NO 3 and N 2 O 5 at night without being photolysis 62,64 . This has been proved by some previous studies 65,66 . A recent observational study in Nanjing found that the high level of volatile organic components (VOCs) concentrations in January 2015, which were emitted by various industrial sources nearby 67 .…”
Section: Resultssupporting
confidence: 64%
“…In this case, the enriched NO 2 atmosphere and dark environment were responsible for generating NO 3 and N 2 O 5 at night without being photolysis 62,64 . This has been proved by some previous studies 65,66 . A recent observational study in Nanjing found that the high level of volatile organic components (VOCs) concentrations in January 2015, which were emitted by various industrial sources nearby 67 .…”
Section: Resultssupporting
confidence: 64%